Factors associated with lesion detection in colonoscopy among different indications. Issue 9 (27th October 2022) - Mangas‐Sanjuan, Carolina; Seoane, Agustin; Alvarez‐Gonzalez, Marco Antonio; Luè, Alberto; Suárez, Adolfo; Álvarez‐García, Verónica; Bujanda, Luis; Portillo, Isabel; González, Natalia; Cid‐Gomez, Lucía; Cubiella, Joaquín; Rodríguez‐Camacho, Elena; et al.
Abstract: Background and objective: Different factors may influence colonoscopy performance measures. We aimed to analyze procedure‐ and endoscopist‐related factors associated with detection of colorectal lesions and whether these factors have a similar influence in the context of different colonoscopy indications: positive fecal immunochemical test (+FIT) and post‐polypectomy surveillance colonoscopies. Methods: This multicenter cross‐sectional study included adults aged 40–80 years. Endoscopists ( N  = 96) who had performed ≥50 examinations were assessed for physician‐related factors. Adenoma detection rate (ADR), adenomas per colonoscopy rate (APCR), advanced ADR, serrated polyp detection (SDR), and serrated polyps per colonoscopy rate (SPPCR) were calculated. Results: We included 12, 932 procedures, with 4810 carried out after a positive FIT and 1967 for surveillance. Of the 96 endoscopists evaluated, 43.8% were women, and the mean age was 41.9 years. The ADR, advanced ADR, and SDR were 39.7%, 17.7%, and 12.8%, respectively. Adenoma detection rate was higher in colonoscopies after a +FIT (50.3%) with a more than doubled advanced ADR compared to non‐FIT procedures (27.6% vs. 13.0%) and similar results in serrated lesions (14.7% vs. 13.5%). Among all the detection indicators analyzed, withdrawal time was the only factor independently related to improvement ( p  < 0.001). Regarding FIT‐positive and surveillance procedures, for both indications, withdrawal time was also the only factor associated with a higher detection of adenomas and serrated polyps ( p  < 0.001). Endoscopist‐related factors (i.e., weekly hours dedicated to endoscopy, annual colonoscopy volume and lifetime number of colonoscopies performed) had also impact on lesion detection (APCR, advanced ADR and SPPCR). Conclusions: Withdrawal time was the factor most commonly associated with improved detection of colonic lesions globally and in endoscopies for + FIT and post‐polypectomy surveillance. Physician‐related factors may help to address strategies to support training and service provision. Our results can be used for establishing future benchmarking and quality improvement in different colonoscopy indications.